Pancreatic Masses Advances in Diagnosis and Therapy - Wagh, Mihir S.; Draganov, Peter V. (Springer International Publishing : Imprint: Springer, 2016)
This volume provides a comprehensive, state-of-the art review of the management of pancreatic lesions. The book reviews the differential diagnosis and pathology of different pancreatic lesions, profiles new advances in endoscopic evaluation, highlights new perspectives about imaging modalities, describes current treatment strategies, and provides an algorithmic approach to management of pancreatic tumors. Recently published literature is placed in context with current management recommendations. The text also discusses the latest advances in minimally invasive techniques, such as Endoscopic Retrograde Cholangio-Pancreatography (ERCP) and Endoscopic Ultrasound (EUS). Written by experts in their fields, Pancreatic Masses: Advances in Diagnosis and Therapy is a valuable resource for gastroenterologists, surgeons, and internists that helps guide patient management and stimulate investigative efforts.